2020
DOI: 10.1515/med-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous DLBCL non-GCB type: challenges of a rare case

Abstract: AbstractSeveral types of B-cell lymphomas, including both primary cutaneous lymphomas and systemic lymphomas, may affect the skin, with partially overlapping clinical, morphological and immunohistochemical features. Currently, the World Health Organization (WHO) classification of primary cutaneous B-cell lymphomas does not include diffuse large B-cell lymphomas (DLBCL) and considers leg-type DLBCL the only primary cutaneous DLBCL. Here we report the case of a 72-year-old white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…This strategy consists of observing and treating the patient only when the disease shows systemic symptoms, bulky mass (<7 cm), symptomatic splenomegaly, progressive leukemization, and serum effusions. Follow-up is usually planned every 6 months with a complete skin and lymph node examination (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy consists of observing and treating the patient only when the disease shows systemic symptoms, bulky mass (<7 cm), symptomatic splenomegaly, progressive leukemization, and serum effusions. Follow-up is usually planned every 6 months with a complete skin and lymph node examination (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Associated to treatment, adequate nutrition, muscle rehabilitation and psychological support allow a better chance of recovery, our patient in on reliable example of this [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of cancer patients due to an adequate program of physical activity [23][24][25]34] and impact the cancer survival [7], since it reduces the peak oxygen consumption, improves physical capacity, increases self-esteem, reduces accumulated stress, and promotes relaxation [8,11]. Consequently, physical activity is strongly recommended for healthy individuals to improve cardiorespiratory and muscular fitness, bone health, and in general to reduce the risk of non-communicable diseases, depression, and cognitive decline [11] The correct application of an exercise program may have a beneficial effect in onco-hematologic patients, since it may improve the function of the immune system (regulation of macrophages and natural killer cells interacting with cancer cells) [9,10] and provide a protective effect against cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, a stimulation change may occur due to cellular changes in tissues surrounding the electrodes caused by the displacement of the electrodes, loosening of the electrical connections, defects in the lead, or alterations in the charge of the batteries. Spinal cord stimulation is mainly applied in the failed back surgery syndrome (FBSS), neuropathic pain, peripheral ischemic pain, amputation pain and visceral pain (28,29), and disorders involving chronic pain lasting for years.…”
mentioning
confidence: 99%